2018
DOI: 10.1002/cncr.31645
|View full text |Cite
|
Sign up to set email alerts
|

Genetic determinants of childhood and adult height associated with osteosarcoma risk

Abstract: Background: Although increased height has been associated with osteosarcoma risk in previous epidemiologic studies, the relative contribution of stature during different developmental time-points remains unclear. Furthermore, how genetic determinants of height impact osteosarcoma etiology remains unexplored. Genetic variants associated with stature in previous genome-wide association studies may be biomarkers of osteosarcoma risk. Methods: We tested the associations between osteosarcoma risk and polygenic sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(50 citation statements)
references
References 53 publications
3
47
0
Order By: Relevance
“…was significantly associated with adult height attainment and osteosarcoma risk after adjustment for multiple comparisons in 864 osteosarcoma cases and 1879 controls of European ancestry [15] . To our best acknowledgement, there were no more reports describing relationship between CILP2 and cancers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…was significantly associated with adult height attainment and osteosarcoma risk after adjustment for multiple comparisons in 864 osteosarcoma cases and 1879 controls of European ancestry [15] . To our best acknowledgement, there were no more reports describing relationship between CILP2 and cancers.…”
Section: Discussionmentioning
confidence: 99%
“…A significant association was also highlighted between polymorphisms in the CILP gene and osteoarthritis progression [14] . But to our best knowledge, few reports have described the relationship between CILP2 and cancers, except one that reported an expression quantitative trait locus, namely rs8103992, was significantly associated with osteosarcoma risk [15] .…”
Section: -Pre-b-cell Leukemia Homeobox 4 (Ncan-cilp2-pbx4) Region Amentioning
confidence: 99%
“…However, the molecular mechanism on CLIP2 affecting lipid metabolism is still unclear. According to Chenan Zhang et al, an expression quantitative trait locus for the CILP2 gene, rs8103992, was statistically signi cantly associated with adult height attainment and osteosarcoma risk after adjustment for multiple comparisons in 864 osteosarcoma cases and 1879 controls of European ancestry [16] . To our best acknowledgment, no more reports were describing the relationship between CILP2 and cancers.…”
Section: Discussionmentioning
confidence: 99%
“…In the preliminary study of TCGA and our cohort analysis, we found that CLIP2 gene showed a tendency of up-expression in colorectal cancer tissues compared with other genes screened by bioinformatics from the TCGA colorectal cancer database. Besides, few reports have described the relationship between CILP2 and cancers, except one that reported an expression quantitative trait locus, namely rs8103992, was statistically signi cantly associated with osteosarcoma risk [16] . In this study, we evaluated CILP2 expression and its correlations with clinicopathological characteristics, such as tumor stages, and overall survival of colorectal cancer patients in the Cancer Genome Altas (TCGA), and furtherly veri ed using immunohistochemistry assay within human colorectal cancer tissues, which may provide a new potential molecular marker for prognostic use of colorectal cancer patients.…”
Section: Introductionmentioning
confidence: 99%
“…According to Chenan Zhang et al, an expression quantitative trait locus for CILP2 gene, rs8103992, was significantly associated with adult height attainment and osteosarcoma risk after adjustment for multiple comparisons in 864 osteosarcoma cases and 1879 controls of European ancestry [15] . To our best acknowledgement, there were no more reports describing relationship between CILP2 and cancers.…”
Section: Discussionmentioning
confidence: 99%